Le personnage de la Finlandaise dans le récit Parmi les falaises (1924) de Maria Boretskaïa, au prisme de la tradition littéraire - Simonova, Olga (OpenEdition, 2025)
The article examines the tradition of the representation of Finnish women in Russian literature, which can be divided into two subtypes. The first, created by Russian realist writers, is the Chukhonka, a character associated with rationality and the desire for independence, but with a bad temper. The second, which is much more ephemeral, is the representation of the Finnish woman associated with nature, as in the poetry of the Romantics and Symbolists. In her story “Among the Cliffs” (1924), the Bolshevik writer Maria Boretskaya created a Finnish female character free from these connotations. Her heroine constructs a Bolshevik and maternal identity.